Do Italian Companies Manage Work-Related Stress Effectively? A Process Evaluation in Implementing the INAIL Methodology. (4th October 2015) - Di Tecco, Cristina; Ronchetti, Matteo; Ghelli, Monica; Russo, Simone; Persechino, Benedetta; Iavicoli, Sergio
Abstract : Studies on Intervention Process Evaluation are attracting growing attention in the literature on interventions linked to stress and the wellbeing of workers. There is evidence that some elements relating to the process and content of an intervention may have a decisive role in implementing it by facilitating or hindering the effectiveness of the results. This study aimed to provide a process evaluation on interventions to assess and manage risks related to work-related stress using a methodological path offered by INAIL. The final sample is composed of 124 companies participating to an interview on aspects relating to each phase of the INAIL methodological path put in place to implement the intervention. INAIL methodology has been defined as useful in the process of assessing and managing the risks related to work-related stress. Some factors related to the process (e.g., implementation of a preliminary phase, workers' involvement, and use of external consultants) showed a role in significant differences that emerged in the levels of risk, particularly in relation to findings from the preliminary assessment. Main findings provide information on the key aspects of process and content that are useful in implementing an intervention for assessing and managing risks related to work-related stress.